A circularly polarized horn antenna with elliptical waveguide polarizer. Issue 12 (24th July 2019) - Yu, Haiyang; Yu, Junsheng; Liu, Xiaoming; Yao, Yuan; Chen, Xiaodong
Abstract: In this article, a circularly polarized horn antenna with elliptical waveguide polarizer is proposed. By converting linear polarization into circular polarization in the elliptical waveguide polarizer, circularly polarized radiation can be realized by the proposed antenna in D‐band. The observation shows that the proposed antenna achieves the impedance bandwidth of 16.7% for S11 < −10 dB from 110 to 130 GHz and the axial‐ratio bandwidth of 11.7% from 114 to 128 GHz. The measured gain of the proposed antenna can reach the range 13.6‐17.82 dBic from 110 to 130 GHz. Besides, the measured normalized beam of the proposed antenna at the far field is able to realize a sidelobe below −25 dB, as well as good axial symmetry. With the elliptical waveguide polarizer, it is obtained that the proposed antenna has the potential application of circularly polarized radiation in millimeter and sub‐millimeter wave band.